2006
DOI: 10.1210/me.2005-0476
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Akt Substrate, AS160, with the Glucose Transporter 4 Vesicle Marker Protein, Insulin-Regulated Aminopeptidase

Abstract: Insulin-regulated aminopeptidase (IRAP), a marker of glucose transporter 4 (GLUT4) storage vesicles (GSVs), is the only protein known to traffic with GLUT4. In the basal state, GSVs are sequestered from the constitutively recycling endosomal system to an insulin-responsive, intracellular pool. Insulin induces a rapid translocation of GSVs to the cell surface from this pool, resulting in the incorporation of IRAP and GLUT4 into the plasma membrane. We sought to identify proteins that interact with IRAP to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 47 publications
1
76
2
Order By: Relevance
“…The Rab Gap, AS160, plays an important role in insulin-dependent GLUT4 trafficking (50), and it has been shown to bind to IRAP in pulldown (51) and vesicle adsorption experiments (52). The intracellular sequence of LRP1 has homologies to that of IRAP, and accordingly, we performed pulldown experiments with cytosolic sequences from IRAP, sortilin, and LRP1, and we blotted for AS160 as show in Fig.…”
Section: Lrp1 C Terminus Binds Akt Substrate Of 160 Kda (As160)-mentioning
confidence: 99%
“…The Rab Gap, AS160, plays an important role in insulin-dependent GLUT4 trafficking (50), and it has been shown to bind to IRAP in pulldown (51) and vesicle adsorption experiments (52). The intracellular sequence of LRP1 has homologies to that of IRAP, and accordingly, we performed pulldown experiments with cytosolic sequences from IRAP, sortilin, and LRP1, and we blotted for AS160 as show in Fig.…”
Section: Lrp1 C Terminus Binds Akt Substrate Of 160 Kda (As160)-mentioning
confidence: 99%
“…The active Rab would then promote vesicle trafficking in an as of yet undefined manner. Alternatively, it has also been proposed that AS160 directly associates with another IRC cargo protein IRAP, and that insulin-dependent Akt phosphorylation results in the dissociation of AS160 from GLUT4 compartment and would also lead to Rab activation [80]. Although these studies have suggested that AS160 serves as the insulin-regulated ratelimiting step in GLUT4 translocation, both an in vitro plasma membrane reconstitution fusion system and in vivo TIRF microscopy measurements indicate that the critical site of insulin regulation is the plasma membrane fusion process downstream of AS160 [23,25].…”
Section: Insulin Signaling Leading To Glut4 Translocationmentioning
confidence: 99%
“…Besides the RabGAP domain at the C terminus, AS160 also has two phosphotyrosine binding domains (PTBs) at the N terminus and a calmodulin binding domain in the middle. The PTBs of AS160 can bind phospholipids (20) as well as the insulin-regulated aminopeptidase (IRAP) that associates with GSVs (21). An N-terminal AS160 fragment was detected in transformed lymphocytes from a human patient bearing the AS160 Arg363Ter mutation (18).…”
mentioning
confidence: 99%